Pengaruh Model Pembelajaran Blanded Learning berbantuan Kahoot terhadap Motivasi dan Kemandirian Siswa - Musrohul Izzati; Heri Kuswanto (Jurnal Pendidikan Informatika (EDUMATIC), 2019)
This research aimed  to know: The Effect of kahoot-assisted Blanded Learning model towards studentsâ€™ motivation and Learning independence in subject of digital simulation for student of XI TKJ at SMK Bajang NW Ajan in the academic years 2019/2020. This research was a quantitative method of transfortation. The research design was a pre-ekperimental design in the form of one group pretest and posttest design. The population wa all students of XI TKJ consisting 30 students. The techniques used to collegt data were questionnaires and observation sheets. The questionnaire was used to measure students motivation and observation sheets. The questionnaire was used to measure students    motivation and observation sheets were used to measure studentsâ€™ learning independence. Analysis tehniques used was to measure studentsâ€™ motivation and observation sheets were used to measure studentsâ€™ learning independence. The analysis technique was the Paired Sample T-tes using SPSS. The test results showed that: (1) there was the influence of kahoot-assisted Blanded Learning models towards studentsâ€™ learning motivation with a significance value of 11.3901,699 and 0,0000,05 (Ï0.05).: (2) there was an influence of blanded learning assisted kaoot-assisted learning model -towards studentsâ€™ learning indepedence  of woyh a significance value of 21.8921,699 and 0,0000,05 (Ï0.05).